Structure and characteristics of fuelwood supply chain in Yobe, Nigeria - Bulama, Ali; Saadun, Norzanalia; Kamarudin, Norizah; Alias, Mohamad Azani; Mohd Nawi, Nolila (Institut Pertanian Bogor, 2022)
Fuelwood commercialization activities provide a source of livelihood in Nigeria. Despite its economic significance, the industry has been kept out of the formal economies due to a lack of supportive data on the structure and characteristics of the industry. This study investigates the structure of the supply chain and examines the chain actors' roles and functions to understand the issues within the supply chain activities. Data were collected through key informants' interviews and observations. The study found that fuelwood business activities were conducted formally by licensed actors and informally by non-licensed actors. Benefits received and issues experienced by actors were related to the formality of the business. Heavy reliance on natural forests for fuelwood production among chain actors can add pressure on the forest resources and ecosystem. Therefore, significant intervention is needed for the industry which includes policy and programs related to fuelwood plantation and management, government support, licensing education, and collaborations among all stakeholders to improve supply chain activities.